A COMPARISON BETWEEN GAMES AND GRAMMAR TRANSLATION METHODS IN IMPROVING PUPILS VOCABULARY ACHIEVEMENT - Pandensolang, Sri Yuliana; Panjaitan, Nelson B. (Journal of Language Pedagogy, 2011)
In teaching English, the teaching method determine the improvement of vocabulary achievement. Therefore, this study titled "A comparison between Games and Grammar Translation Methods in improving pupils Vocabulary Achievement." The participants involved in this study were 62 grade 5 pupils of SDN Karyawangi Parongpong, Bandung. The grade SB composed of 29 pupils, while the grade SC composed of 33 pupils. This study was divided into three steps: (1) the pretest, (2) the implementation of Games and Grammar Translation Method (GTM). (3) and the posttest. In the pretest and posttest, the multiple choice and essays form was administered to them. As the treatment, the researcher taught Games to one group, and GTM to the other group. At the end of the study, the result proved that the vocabulary achievement of the pupils taught using Grammar Translation Method is higher compared to those taught by Games.